PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN GADGET TERHADAP MOTIVASI BELAJAR IPAS SISWA DI SD SARASWATI 2 DENPASAR - Ari Setyawati, Ni Kadek; Ni Wayan Sariani Binawati; I Made Sukariawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning motivation is an important factor influencing students' learning achievement. The implementation of innovative learning models supported by technology is expected to improve students' motivation, particularly in Natural and Social Sciences (IPAS) learning. This study aimed to determine the effect of the Problem Based Learning (PBL) model assisted by gadgets on students' learning motivation at SD Saraswati 2 Denpasar. This study employed a quantitative approach with a quasi-experimental method using a pretest-posttest control group design. The sample consisted of 49 fifth-grade students, including 25 students in the experimental class and 24 students in the control class. Data were collected using a learning motivation questionnaire that had passed validity and reliability testing. Data were analyzed using descriptive statistics, normality test, homogeneity test, and Independent Sample t-test. The findings indicated that the average learning motivation score of the experimental class increased from 73.64 to 80.32, while the control class increased from 71.00 to 74.88. The Independent Sample t-test showed a significance value (Sig. 2-tailed) of 0.004 (<0.05), indicating that the Problem Based Learning model assisted by gadgets had a significant effect on students' learning motivation. Therefore, the implementation of the PBL model assisted by gadgets can be used as an alternative learning model to improve elementary school students' learning motivation in IPAS.